A DNA segment encoding the anticodon stem/loop of tRNA determines the specific recombination of integrative-conjugative elements in Acidithiobacillus species. Issue 4 (4th May 2018) - Castillo, Andrés; Tello, Mario; Ringwald, Kenneth; Acuña, Lillian G.; Quatrini, Raquel; Orellana, Omar
ABSTRACT: Horizontal gene transfer is crucial for the adaptation of microorganisms to environmental cues. The acidophilic, bioleaching bacterium Acidithiobacillus ferrooxidans encodes an integrative-conjugative genetic element (ICE Afe1 ) inserted in the gene encoding a tRNA Ala . This genetic element is actively excised from the chromosome upon induction of DNA damage. A similar genetic element (ICE AcaTY .2 ) is also found in an equivalent position in the genome of Acidithiobacillus caldus . The local genomic context of both mobile genetic elements is highly syntenous and the cognate integrases are well conserved. By means of site directed mutagenesis, target site deletions and in vivo integrations assays in the heterologous model Escherichia coli, we assessed the target sequence requirements for site-specific recombination to be catalyzed by these integrases. We determined that each enzyme recognizes a specific small DNA segment encoding the anticodon stem/loop of the tRNA as target site and that specific positions in these regions are well conserved in the target attB sites of orthologous integrases. Also, we demonstrate that the local genetic context of the target sequence is not relevant for the integration to take place. These findings shed new light on the mechanism of site-specific integration of integrative-conjugative elements in members of Acidithiobacillus genus.